Efecto de la aplicación de los flavonoides sobre la involución uterina en el puerperio bovino, en la hacienda Sociedad Agropecuaria Callo Mulaló - Barona Sevilla, Francisco Alejandro (2017)
The objective of the present investigation was to evaluate the effect of the application of 45 percent flavonoids on uterine involution during bovine puerperium in a population of 25 milk cows Holstein Friesian under exclusion and inclusion criteria, of which the experimental group comprised 20 and the control group 5. The methodology used in this study was the ultrasonographic measurement of the diameter of cervix, wall of cervix, uterus, wall of uterus and ovaries at day 10 and 21 postpartum to determine the percentage of uterine involution, endometrial cytology was also performed to find Bacterial genera in the uterus. The data were tabulated in Excel and analyzed in Stata, where measures of central tendency were studied, later ttest was performed inside each group to compare the measurements at day 10 postpartum with day 21 postpartum. The control group had a decrease in diameter of the cervix of 1.26cm, wall of cervix of 0.32cm, uterus of 0.74cm and wall of uterus of 0.14cm; And an increase of the right ovary diameter of 0.62cm, left ovary of 0.50cm, and percentage of uterine involution 28 percent; In the experimental group decreased diameter of cervix 0.85cm, wall of cervix 0.72cm, uterus 2.39cm and wall of uterus 0.46cm; And increased the diameter of the right ovary 0.40cm, left ovary 0.64cm and percentage of uterine involution 38.75 percent. Finally ANOVA was performed to compare between groups by means of p value of the structures, which showed that there were no significant differences for the diameter of cervix with 0.463, uterus 0.329, wall of uterus 0.988, right ovary 0.210 and left ovary 0.902, however We found significant differences for cervical wall diameter with 0.016 and percentage of uterine involution with 0.000 forming subgroups in which the control group formed the subgroup a and the experimental group subgroup b. Finally, the null hypothesis is accepted since the flavonoids did not influence ovarian and cervical involution, however, flavonoids significantly influenced the uterine involution rejecting the null hypothesis.